“Informative representation” for the vulnerability analysis of anthropic landscape. two different areas in comparison: the historical center of St. Elia Fiume Rapido (FR) and the mining site of Coreno Ausonio. - Assunta Pelliccio (Disegnare con, 2013)
The main riscks of the landscape are the overexploitation of the soil and a high physical vulnerability of our country determined by considerable seismic and volcanic activities, and by the peculiar geomorphological and hydrogeological pattern. This risk needs to be mitigated through a careful analysis of the criticity levels in the different geographical areas and by developing strategies based on requirements and operational guidance. In this paper two different procedures for vulnerability analysis are described, designed for completely different landscape areas. The first case concerns the historical center of Sant’Elia Fiumerapido, in the province of Frosinone, with the objective of analysing the town and its exposure to natural factors of degradation. The second case is the basin of Coreno Ausonio, in the province of Latina, deeply marked by intense mining activities. These two cases constitute examples where the "Informative Representation" allows an immediate reading of the involved components with the aim, in the first case to preserve the evidence of the past, in the second case to protect the environment from uncontrolled human activities.